Teachers’ stress experiences during COVID-19-related emergency remote teaching: Results from an exploratory study - Vergine, Ilaria; Gatti, Flora; Berta, Giulia; Marcucci, Giulia; Seccamani, Alice; Galimberti, Carlo (Frontiers in Education, 2022)
The study provides a portrait of teachers’ stress experience in the face of the needed introduction of information systems (IS) during COVID-19-related emergency remote teaching. Researchers contacted the headmasters at several Italian schools, who choose teacher’s representatives. The latters shared the online questionnaire among colleagues; the teachers voluntarily decided to participate. The cross-sectional study involved 237 Italian teachers (81.5% female; Mage = 50.20; SDage = 8.87). This survey wanted to detect information systems-related distress and eustress on the job, and technostress creators and inhibitors. Descriptive statistics, correlational analyses, and a multiple regression model using structural equation modeling were run. As according to the model, IS-related distress and eustress on the job were the dependent variables, technostress creators and inhibitors the independent ones, and respondents’ gender and age the control ones. Both technostress creators and inhibitors showed significant relationships with IS-related distress and eustress. Technostress creators showed a positive relationship with IS-related distress and a negative one with IS-related eustress; conversely, technostress inhibitors showed an opposite pattern of relationships. Only technostress creators significantly associate to both age and gender in the model, suggesting that older, female teachers tended to experience more technostress creators. Due to the increases in remote work, the awareness of IS-related stress experiences represents a key factor to evaluate work-related risks and prevent stress-related problems. The results from this study suggest that using technologies can represent both a threat to one’s well-being, highlighting the need to provide adequate trainings and support, but also a resource for personal enrichment.